A Unique Case of a Malignant Sertoli Cell Tumour with Cutaneous Metastasis - C. Blick; S. Abdelhadi; D. Bailey; J. Kelleher; A. Muneer (The Scientific World Journal)
Pure Sertoli cell tumours (SCTs) represent less than 1% of testicular neoplasms and malignant forms are rare. We present a unique case of a 69-year-old man who initially underwent inguinal orchidectomy for a malignant SCT. He then subsequently developed a paraumbilical cutaneous lesion which was histologically identical to the primary tumour. SCTs rarely metastasise. This is the first case of SCT with cutaneous metastasis described in the literature.